¿Por qué la economía necesita "su Campo de Higgs"? - Mora Jiménez, Henry (2018)
In fundamental physics, the Higgs field acts as a mechanism that generates mass in nonzero mass particles, thus traveling with limited mobility, not close to the speed of light. The field of economics has not developed an equivalent theory that would explain the so-called viscosities and rigidities that prevent the automatic adjustment of prices and the free mobility of factors. It is important to ask what that viscosity is and what characteristics it presents. Is it perhaps an unknown or ignored "economic field"?